2019
DOI: 10.1016/j.soildyn.2019.01.030
|View full text |Cite
|
Sign up to set email alerts
|

A 2.5D time-frequency domain model for railway induced soil-building vibration due to railway defects

Abstract: This is a repository copy of A 2.5D time-frequency domain model for railway induced soil-building vibration due to railway defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…This work uses the methodology presented in Reference [47] to model the source-propagation subsystem (S(f ), P (f )). Once it is solved for the source-propagation subsystem, it can be used to compute the building vibration A(f ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This work uses the methodology presented in Reference [47] to model the source-propagation subsystem (S(f ), P (f )). Once it is solved for the source-propagation subsystem, it can be used to compute the building vibration A(f ).…”
Section: Methodsmentioning
confidence: 99%
“…5. Soil-structure transfer function is combined with free-field vibration u g [47] to obtain building response u by railway traffic (Equation ( 4)).…”
Section: Methodology Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…One reason is that the use of a prediction model that directly allows for the non-Hertzian wheel-rail contact and vehicle dynamics and also includes three dimensional calculations of the ground response would be highly computationally expensive [4]. In order to overcome the computational cost of such a complex model there have been a few studies in the literature that use a hybrid approach to predict ground-borne vibration due to impacts [5,6,7], but these focus mainly on singular defects such as joints and wheel flats.…”
Section: Introductionmentioning
confidence: 99%
“…Although single simulation were firstly adopted to predict the effect of a running train on the generated ground wave propagation [1,2], recent research suggested to split the problem in order to take into account specific complex phenomena [3]. Theferore, Kouroussis et al designed and validated a two-step model [4,5,6] that furnishes a sufficiently accurate prediction of the vibrations generated on the ground for different types of soil. This model uses a first step to estimate the forces applied on the soil through a fully coupled model of the vehicle, the track and a reduced coupled lumped masses (CLM) model of the soil [7].…”
Section: Introductionmentioning
confidence: 99%